Native Valve Endocarditis due to Ralstonia pickettii: A Case Report and Literature Review - Joseph Orme; Tomas Rivera-Bonilla; Akil Loli; Negin N. Blattman (Case Reports in Infectious Diseases)
Ralstonia pickettii is a rare pathogen and even more rare in healthy individuals. Here we report a case of R. pickettii bacteremia leading to aortic valve abscess and complete heart block. To our knowledge this is the first case report of Ralstonia species causing infective endocarditis with perivalvular abscess.